Congenital Extrahepatic Portosystemic Shunts (Abernethy Malformation): An International Observational Study. Issue 2 (19th August 2019) - Baiges, Anna; Turon, Fanny; Simón‐Talero, Macarena; Tasayco, Stephanie; Bueno, Javier; Zekrini, Kamal; Plessier, Aurélie; Franchi‐Abella, Stéphanie; Guerin, Florent; Mukund, Amar; Eapen, C.E.; Goel, Ashish; et al.
Abstract : Congenital extrahepatic portosystemic shunt (CEPS) or Abernethy malformation is a rare condition in which splanchnic venous blood bypasses the liver draining directly into systemic circulation through a congenital shunt. Patients may develop hepatic encephalopathy (HE), pulmonary hypertension (PaHT), or liver tumors, among other complications. However, the actual incidence of such complications is unknown, mainly because of the lack of a protocolized approach to these patients. This study characterizes the clinical manifestations and outcome of a large cohort of CEPS patients with the aim of proposing a guide for their management. This is an o bservational, multicenter, international study. Sixty‐six patients were included; median age at the end of follow‐up was 30 years. Nineteen patients (28%) presented HE. Ten‐, 20‐, and 30‐year HE incidence rates were 13%, 24%, and 28%, respectively. No clinical factors predicted HE. Twenty‐five patients had benign nodular lesions. Ten patients developed adenomas (median age, 18 years), and another 8 developed HCC (median age, 39 years). Of 10 patients with dyspnea, PaHT was diagnosed in 8 and hepatopulmonary syndrome in 2. Pulmonary complications were only screened for in 19 asymptomatic patients, and PaHT was identified in 2. Six patients underwent liver transplantation for hepatocellular carcinoma or adenoma. Shunt closure was performed in 15 patients with improvement/stability/cure of CEPS manifestations. Conclusion: CEPS patients may develop severe complications. Screening for asymptomatic complications and close surveillance is needed. Shunt closure should be considered both as a therapeutic and prophylactic approach.